Territory independence according to the Constitution of the Republic of Iraq for the year 2005 - يونس, مها بهجت; عاجب, رائد حمدان (Journal of Legal Sciences, 2019)
One of the constituents of the autonomy of constituent units of the federal State is the existence of an independent legal existence and the right to self-organization, ie, the ability to organize itself freely and at its own volition, without being imposed by the federal authorities. It is the federal states or regions that establish their own constitutions as well as their domestic laws, political system and government regulations, in a manner not inconsistent with the federal constitution. Such an idea and its application in Iraq was the subject of our study entitled "Organic Independence of the Federal Regions in accordance with the Constitution of the Republic of Iraq of 2005".